INNOVATIVE APPROACHES TO TEACHING FOREIGN LANGUAGES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The word innovative approaches to teaching foreign languages has become one of the important parts of the education system today. Globalization processes, economic relations and cultural interactions require knowledge of foreign languages. This makes it necessary to develop new approaches and methods for teachers and students. Innovative approaches to teaching foreign languages not only facilitate language learning, but also make the learning process interesting and effective. This article provides information about modern innovative approaches used in teaching foreign languages, their advantages and practical application